2000
DOI: 10.1111/j.1553-2712.2000.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Discharge of Patients with Presumed Opioid Overdose: Development of a Clinical Prediction Rule

Abstract: Abstract. Objective: To develop a clinical prediction rule to identify patients who can be safely discharged one hour after the administration of naloxone for presumed opioid overdose. Methods: Patients who received naloxone for known or presumed opioid overdose were formally evaluated one hour later for multiple potential predictor variables. Patients were classified into two groups: those with adverse events within 24 hours and those without. Using classification and regression tree methodology, a decision r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…Comatose or semicomatose states may increase the risk for developing systemic complications including aspiration pneumonia. A previous study in Canada also identified an altered consciousness level as one of the predictors for admission to hospitals in patients with opioid overdose [18]. Elevated WBC at admission was a risk factor for a prolonged LOS in this study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Comatose or semicomatose states may increase the risk for developing systemic complications including aspiration pneumonia. A previous study in Canada also identified an altered consciousness level as one of the predictors for admission to hospitals in patients with opioid overdose [18]. Elevated WBC at admission was a risk factor for a prolonged LOS in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Both the systemic complications and the cardiotoxic states may explain the delayed recovery in these patients. The prediction rules developed in previous studies for patients with opioid DO also identified abnormal HR including both tachycardia and bradycardia as an increased risk for admission [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although abbreviated observation periods may be adequate for patients with fentanyl, morphine, or heroin overdose, 102,109,[120][121][122][123] longer periods of observation may be required to safely discharge a patient with life-threatening overdose of a long-acting or sustained-release opioid. 93,124,125 Naloxone administration in post-cardiac arrest care may be considered in order to achieve the specific therapeutic goals of reversing the effects of long-acting opioids (Class IIb, LOE C-EO).…”
Section: Observation and Post-resuscitation Carementioning
confidence: 99%
“…26,53,54 Published guidelines for the management of opioid intoxication were developed on the basis of data from patients with heroin overdose and should not be applied to patients with opioid analgesic overdose. 55,56 …”
Section: Discussionmentioning
confidence: 99%